Geometric and Static Analysis of the Historical Trusses in Roman Catholic Church of the Holy Kozma and Damian in the Abramová Village - Krušinský Peter; Capková Eva; Gocál Jozef; Holešová Michaela (Civil and Environmental Engineering, 2015)
The truss of the Roman Catholic Church of the holy Kozma and Damian was managed to date to the year 1470/71d. It represents one of the few well-preserved medieval structures in this region. The form of roofs is a typical for rafter collar-beam construction without stiffening frame. The geometrical analysis of the main roofs trusses is based on logical dependencies and a description of a process in the truss design, pointing to evaluative relations resulting especially from the Pythagorean Geometry. Consequently, a spatial numerical model of the roof structure was developed in order to perform a static analysis of the roof structure in accordance with present standards. Due to the fact that during the diagnostic survey there were noted some missing structural elements in the roof construction (angle braces), in further analysis, an attention was paid to the importance of the selected structural elements and their role in the construction of the truss itself.